Keefektifan Model Pembelajaran Kooperatif Tipe NHT dan Model Pembelajaran Kooperatif Tipe Jigsaw dalam Menentukan Unsur Intrinsik Cerpen Kelas IX SMP Negeri 2 Mamuju - Arsam Akil; Akmal Hamsa; Usman Usman (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research aims to: (1) examine the effectiveness of the NHT type cooperative model in learning to determine the intrinsic elements of short stories; (2) examine the effectiveness of the jigsaw type cooperative model in learning to determine the intrinsic elements of short stories; and (3) prove the effectiveness of the Numbered Head Together (NHT) type cooperative model and the jigsaw type cooperative model in learning to determine the intrinsic elements of short stories. This research is experimental research. The population in this study was class IX students at SMP Negeri 2 Mamuju, totaling 324 students consisting of eleven classes. From the eleven classes, samples were determined using a lottery technique. The sample in this study was 54 people consisting of class IX 3 and class IX 4. After determining the sample, the data was then collected using a test technique, namely by measuring students' understanding of the intrinsic elements of short stories. The variables examined in this research are the Numbered Head Together (NHT) cooperative model, the jigsaw cooperative model, and the ability to analyze the intrinsic elements of short stories.. This research obtained the following results: (1) The Numbered Head Together (NHT) learning model can increase students' understanding in analyzing the intrinsic elements of short stories for class IX students at SMP Negeri 2 Mamuju. This was proven from the pre-test score of 69.41 to 78.40 in the post-test score; (2) The jigsaw learning model can improve students' understanding in analyzing the intrinsic elements of short stories for class IX students at SMP Negeri 2 Mamuju. This is proven from the pre-test score of 60.48 to 77.25 in the post-test score; and (3) Based on the results of the hypothesis test Sig. (2-tailed) shows the same value in both learning models of 0.659. This shows that both learning models are effectively used. However, this is different from the tcount value obtained, namely 0.444. The tcount value is 0.444 from the ttable value of 2.055, therefore, the hypothesis (H0) is accepted and (H1) is rejected so that the NHT type cooperative learning model is more effective than the jigsaw type cooperative learning model in analyzing the intrinsic elements of class IX students' short stories at SMP Negeri 2 Mamuju.